Barriers to shared decision-making with women of reproductive age affected by a chronic inflammatory disease: a mixed-methods needs assessment of dermatologists and rheumatologists. Issue 6 (16th June 2021) - Murray, Suzanne; Augustyniak, Monica; Murase, Jenny E; Fischer-Betz, Rebecca; Nelson-Piercy, Catherine; Peniuta, Morgan; Vlaev, Ivo
Abstract : Objectives: The main study objective was to identify challenges and barriers experienced by dermatologists and rheumatologists when engaging women of reproductive age in shared decision-making (SDM) related to treatment and management of chronic inflammatory disease (CID) before, during and after pregnancy. Design: A mixed-methods study was conducted, employing (1) semistructured interviews, (2) an online survey and (3) triangulation of findings. Participants: 524 dermatologists and rheumatologists entered the study; 495 completed it; 388 met inclusion criteria for analysis. Participants were included if actively practising in Germany (GER), the UK or the USA; had a minimum 5% caseload of female patients of reproductive age with either axial spondyloarthritis, psoriasis, psoriatic arthritis or rheumatoid arthritis; and had experience prescribing biologics. Results: 48 interviews and 340 surveys were analysed. Interviews underscored dermatologists and rheumatologists' suboptimal integration of SDM in clinical practice. In the survey, 90% (n=305) did not know about SDM models. A perceived lack of competency counselling patients on pregnancy and family planning was also identified during interviews. Among the survey sample, 44% (n=150) of specialists agreed they preferred leaving pregnancy-related discussions to obstetricians and/or gynaecologists and 57% (n=189) reported having suboptimal skills discussing contraceptive methods with patients. Another finding that emerged from interviews was the perception that all biologics are strictly contraindicated during pregnancy. Suboptimal knowledge was noted among 57% (n=95) of dermatologists and 48% (n=83) of rheumatologists surveyed in that regard, with a statistically significant difference by country among dermatologists (GER: 42% vs UK: 71% vs USA: 57%, p=0.015). Conclusions: This study identified low levels of knowledge, skill and confidence, as well as attitudinal issues, that explain why SDM is not fully integrated in dermatology and rheumatology clinical practice. Blended-learning interventions are recommended to assist CID specialists in developing effective communication and patient engagement competencies.